In vivo antihyperglycaemic and antihyperlipidemic activities and chemical constituents of Solanum anomalum - Jude E. Okokon (Biomedicine & Pharmacotherapy, 2022)
Solanum anomalum is a plant used ethnomedically for the treatment of diabetes. The study was aimed to validate ethnomedical claims in rat model and identify the likely antidiabetic compounds. Leaf extract (70–210 mg/kg/day) and fractions (140 mg/kg/day) of S. anomalum were evaluated in hyperglycaemic rats induced using alloxan for effects on blood glucose, lipids and pancreas histology. Phytochemical characterisation of isolated compounds and their identification were performed using mass spectrometry and NMR spectroscopy. Bioinformatics tool was used to predict the possible protein targets of the identified bioactive compounds. The leaf extract/fractions on administration to diabetic rats caused significant lowering of fasting blood glucose of the diabetic rats during single dose study and on repeated administration of the extract. The hydroethanolic leaf extracts also enhanced glucose utilization capacity of the diabetic rats and caused significant lowering of glycosylated hemoglobin levels and elevation of insulin levels in the serum. Furthermore, triglycerides, LDL-cholesterol, and VLDL-cholesterol levels were lowered significantly, while HDL–cholesterol levels were also elevated in the treated diabetic rats. There was absence or few pathological signs in the treated hyperglycaemic rat pancreas compared to that present in the pancreas of control group. Diosgenin, 25(R)-diosgenin-3-O-α-L-rhamnopyranosyl-(1→4)-β-D-glucopyranoside, uracil, thymine, 1-octacosanol, and octacosane were isolated and identified. Protein phosphatases along with secreted proteins are predicted to be the major targets of diosgenin and the diosgenin glycoside. These results suggest that the leaf extract/fractions of S. anomalum possess antidiabetic and antihyperlipidemic properties, offer protection to the pancreas and stimulate insulin secretion, which can be attributable to the activities of its phytochemical constituents.